2016
DOI: 10.1002/anie.201600638
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Phosphorylated Histone H2A at Tyr57 Reveals Insight into the Inhibition Mode of the SAGA Deubiquitinating Module

Abstract: Monoubiquitination of histone H2B plays a central role in transcription activation and is required for downstream histone methylation events. Deubiquitination of H2B by the Spt-Ada-Gcn5 acetyltransferase (SAGA) coactivator complex is regulated by a recently discovered histone mark, phosphorylated H2AY57 (H2AY57p), which inhibits deubiquitination of H2B by the SAGA complex as well as restricting demethylation of H3 and increasing its acetylation. Evidence for the effect of H2AY57p however, was indirect and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 55 publications
0
46
0
1
Order By: Relevance
“…The mechanism indicated that Y57ph could inhibit the access of Spt‐Ada‐Gcn5 acetyltransferase (SAGA) complex to nucleosome and lead to the decrease in deubiquitination ability of the complex, and thus the amount of H2B ubiquitination increased, which plays multiple roles in transcription activation (Figure a). Brik and Wolberger's work supported the hypothesis employing the chemically synthesized Y57ph‐H2A and K120ub‐H2B . The result of in vitro deubiquitination assay indicated that Y57ph inhibited access of the SAGA complex to the nucleosome surface.…”
Section: Chemical Protein Synthesis That Advances Research On Histonementioning
confidence: 62%
“…The mechanism indicated that Y57ph could inhibit the access of Spt‐Ada‐Gcn5 acetyltransferase (SAGA) complex to nucleosome and lead to the decrease in deubiquitination ability of the complex, and thus the amount of H2B ubiquitination increased, which plays multiple roles in transcription activation (Figure a). Brik and Wolberger's work supported the hypothesis employing the chemically synthesized Y57ph‐H2A and K120ub‐H2B . The result of in vitro deubiquitination assay indicated that Y57ph inhibited access of the SAGA complex to the nucleosome surface.…”
Section: Chemical Protein Synthesis That Advances Research On Histonementioning
confidence: 62%
“…Peptide 3a contains the Dbz moiety at the C‐terminal Thr‐370. As the Dbz peptide precursor 3a could not be converted into the Nbz form by using 4‐nitrophenylchloroformate in DCM, we repeated the reaction in DMF: indeed, Brik and coworkers reported that the use of DMF instead of DCM could convert Dbz into Nbz on a peptide bearing a C‐terminal leucine . Unfortunately, in our case, the use of DMF did not solve the problem, and no Nbz peptide was formed (probably, because of the presence of the β‐branched threonine).…”
Section: Discussionmentioning
confidence: 81%
“…Modeling of H2A-Y57p in the structure of the DUB module bound to a ubiquitinated nucleosome [34] indicated that this newly discovered histone PTM has the potential to alter interactions between the arginine anchor and the acidic patch (Figure 1C). This hypothesis was confirmed through use of a fully synthetic strategy to incorporate phosphotyrosine into histone H2A at Y57 [39]. Nucleosomes containing H2A-Y57p and H2B-Ub made by native chemical ligation [40] were used to confirm that this phosphorylation indeed inhibits DUB module activity in vitro [39].…”
Section: Docking Of the Saga Dub Module On Ubiquitinated Nucleosomesmentioning
confidence: 97%
“…This hypothesis was confirmed through use of a fully synthetic strategy to incorporate phosphotyrosine into histone H2A at Y57 [39]. Nucleosomes containing H2A-Y57p and H2B-Ub made by native chemical ligation [40] were used to confirm that this phosphorylation indeed inhibits DUB module activity in vitro [39]. …”
Section: Docking Of the Saga Dub Module On Ubiquitinated Nucleosomesmentioning
confidence: 97%